Perilaku Sedentary pada Remaja Akhir Berdasarkan Banyaknya Akun Media Sosial yang Dimiliki - Etika, Arif Nurma; Agnes, Yeni Lufiana Novita; Yunalia, Endang Mei; Prayogi, Ines Septiya (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2023)
Non-communicable diseases including cardiovascular disease, diabetes and cancer are the number 1 killers in the world. According to the Indonesian Ministry of Health, the incidence of non-communicable diseases in Indonesia increase every year. One of the main factors causing non-communicable diseases is sedentary lifestyle. Sedentary lifestyle are activities that all types of activities need very little caloric (< 1.5 METs). Currently, the use of social media among adolescents is massive. This study aims to identify sedentary behavior in late adolescents based on the amount of social media they have. This research was a correlational analytical research with a cross sectional approach. The sample were 193 students of the Faculty of Health in Kediri. The data were collected using snowball sampling. The instrument used in this study was a modified Sedentary Behaviour Questionary (SBQ). The data obtained were analyzed using the Spearman Rank Test. The results of this study showed that 49.7% performed high sedentary behavior. 42% of late adolescences have 4/more social media accounts, 90.7% of late adolescences use social media daily. The results of the Spearman rank test obtained p-value: 0.031 so there was a relationship between the amount of social media and sedentary behavior, and also p-value: 0.036, Correlation Coefficient: 0.615 so that there was a strong relationship between frequent use of social media with sedentary behavior. From the results of the study, it is recommended to reduce the intensity of social media, so that sedentary behavior can also be minimized, and prevent non-communicable diseases.